Toma de decisiones desde el punto administrativo y financiero en empresas familiares, prestadoras del servicio de transporte de carga (2023)
Family business are avery common type of organization in Colombia, in most cases they are created due to knowledge in a certain activity, service or realization of a product, among others. This type of organization, although initially characterized by the union and the same ideals of the family, over time and due to the different opinions changes and ways of seeing the business, nonstrategic decisions are made that make these companies begin to lack liquidity; consequently, it resorts to increasing the indebtedness and the opportunity cost of the business in not taken into account. On the other hand, the transport sector plays a fundamental role in the development of a country, since it allows the economy to grow and determines the competitiveness and development of the region.